Artificial Intelligence Adoption in Human Resources Management - Tabor-Błażewicz, Joanna (Wykorzystanie sztucznej inteligencji w procesach personalnych, 2023)
In recent years, dynamic changes have been observed in organizations stemming from usage of novel technologies. Among others, artificial intelligence application to Human Resources Management is a developing field of study which shows constant growth. The aim of this paper is to recognize the state of AI adoption in HR departments with a special concern on advantages and disadvantages, attitudes and state of knowledge of HR professionals basing on the results of the literature review as well as empirical research. A systematic review of world literature was carried out using the following databases: Proquest, EBSCO, Emerald, JSTOR, Science Direct and BAZEKON. The results were supplemented with conclusions from quantitative research conducted on the sample of 50 HR professionals. The most visible application of AI can be observed in recruitment and selection although other HR processes may also benefit from it. AI can improve the work of HR departments. The most often mentioned advantage was a possibility to automate routine tasks, while the lack of empathy and “human” approach prevailed among disadvantages. Few companies have implemented or plan to implement AI in HRM in the near future which is confirmed by other studies stating that the application of AI has not advanced as expected.
Tabor-Błażewicz, J. (2023). Artificial Intelligence Adoption in Human Resources Management. In M. Hajdas (Ed.), Game Changers in Management (pp. 30-43). Publishing House of Wroclaw University of Economics and Business.
Keywords: artificial intelligence; HR department; HR professionals; HR processes; sztuczna inteligencja; dział HR; specjaliści HR; procesy HR